Atopic dermatitis in adults: A cross-sectional study in the department of dermatology, Antananarivo, MadagascarCapsule Summary - Fandresena Arilala Sendrasoa, MD; Samson Léophonte Ramily, MD; Tsiory Iarintsoa Razafimaharo, MD; Irina Mamisoa Ranaivo, MD; Malalaniaina Andrianarison, MD; Onivola Raharolahy, MD; Volatantely Ratovonjanahary, MD; Naina Harinjara Razanakoto, MD; Mendrika Fifaliana Rakotoarisaona, MD; Noroiarisoa Andriamanantena, MD; Lala Soavina Ramarozatovo, MD; Rapelanoro Rabenja Fahafahantsoa, MD (Elsevier, 2021)
Background: Although atopic dermatitis (AD) is becoming a pressing public health concern in the world, Madagascar is underrepresented in the AD literature. Objective: We aimed to study the demographic and clinical pattern of AD in adult dermatology outpatients. Methods: A cross-sectional study was conducted in the Department of Dermatology, University Hospital, Antananarivo, Madagascar. Patients >15 years old with a registered diagnosis of AD, from January 2010 to February 2019, were included. AD was diagnosed by a dermatologist according to Hanifin and Rajka criteria. The severity of AD was assessed using scoring atopic dermatitis (SCORAD). Results: Forty-two cases of AD were included. The prevalence was 0.5%. The median patient age was 37 years. The age of onset of AD was before the age of 15 years in 38% of the patients and after the age of 15 years in 61.9% of the patients. There was a female preponderance (female to male ratio, 2:1), but no correlation was found between sex and the severity of AD. People living in urban areas were the most affected. According to SCORAD, 37 cases presented moderate AD and 2 cases presented severe AD. Conclusion: The prevalence of AD in adult dermatology outpatients is still low, and moderate AD is the most frequent form, according to SCORAD.